Gambaran Radiografi Penyakit Periodontal pada Kucing Jantan Lokal Berambut Pendek di Kampus Jatinangor Universitas Padjadjaran - Puspitasari, Ajeng; Amaliya, Amaliya; Rahmiati, Dwi Utari (Jurnal Veteriner, 2021)
Periodontal disease is the most common disease affecting pet animals including cats and dogs.  This disease can cause pain and discomfort affecting the animal’s life quality.  The purpose of this study is to evaluate periodontal disease from dental radiographs taken from male domestic short hair cats.  Eight male domestic short hair cats from Universitas Padjadjaran Jatinangor campus were recruited for the study.  This study observed several changes within the periodontium from dental radiography with simple quantification and analyzed using descriptive analysis.  Dental radiographs were taken on the second right mandibula premolar (408).  Several changes found in the dental radiography including widening of the periodontal ligament, bone loss and furcation involvement.  This study shows varied changes in the periodontium due to the cat’s immune responses.  The examined cats were experiencing widening of the periodontal ligament, bone loss and furcation involvement (37.5%, 25% and 87.5%) respectively.  All cats examined were experiencing periodontal disease.